The influence of ethical dilemmas in the accounting - Hugo Palácios; Joaquim Sant´ana Fernandes; Cristina Gonçalves; Gabriela Gonçalves; Cátia Sousa (Tourism & Management Studies, 2017)
In this study a theoretical model of five dimensions is explained – Rest (1986) ethical decision making process; Jones (1991) moral intensity; need for cognition; personal attributes and financial information - in order to understand the conditions that lead policymakers to manipulate information and to understand the ethical issues in decision-making that lead or not, to a more useful accounting. The sample, by convenience, consisting of 442 individuals and this empirical study was conducted through a survey by an online questionnaire. Data collection was performed using SurveyMonkey software and the model analysed by Structural Equation Analysis method. A structural model was obtained, seeming to indicate that the process of ethical and moral intensity decisions is associated with the individual need for cognition. The utility of accounting, preparation and presentation of financial statements are positively related to the educational level. In this sense, the results and the profitability of capital influence the moral intensity, it seems possible to conclude about the positive influence of academic ethics intention and accounting utility.